Independent Umrah Policy: Between Ideality and Reality - Ahmad Mustofa; Abdul Rozaq (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to analyze the dynamics of the implementation of the Independent Umrah policy in Indonesia using the Adaptive and Networked Implementation Theory framework proposed by Hupe and Hill (2016) and the Projection Model by Jensen and Johansson (2018). The Independent Umrah policy is an integral part of the reform and digital transformation agenda of the public service sector, particularly in the management of the Umrah pilgrimage, realized through the development and utilization of the SISKOPATUH system. This system is designed to provide pilgrims with more direct and autonomous access to manage the Umrah departure process without complete dependence on conventional Umrah travel agencies. This study employed a qualitative approach, with data collection techniques consisting of in-depth interviews with independent Umrah pilgrims and analysis of related policy documents and regulations. The results indicate a significant gap between the ideals of the policy, which focuses on service efficiency, process transparency, and strengthening pilgrim independence, and the reality of implementation on the ground. Various obstacles were identified, such as low digital literacy levels among pilgrims, resistance from travel agencies who felt their role was being reduced, and limited infrastructure readiness and technical support from the government. Further analysis shows that the successful implementation of the Independent Umrah policy is greatly influenced by the effectiveness of cross-actor collaboration, the flexibility of the implementation network, and the government's adaptive capacity in responding to evolving social and institutional dynamics.